Activity-Based Therapies for Repair of the Corticospinal System Injured during Development - Friel, Kathleen M.; Williams, Preston T. J. A.; Serradj, Najet; Chakrabarty, Samit; Martin, John H. (Frontiers in Neurology, 2014)
This review presents the mechanistic underpinnings of corticospinal tract (CST) development, derived from animal models, and applies what has been learned to inform neural activity-based strategies for CST repair. We first discuss that, in normal development, early bilateral CST projections are latter refined into a dense crossed CST projection, with maintenance of sparse ipsilateral projections. Using a novel mouse genetic model, we show that promoting the ipsilateral CST projection produces mirror movements, common in hemiplegic cerebral palsy (CP), suggesting that ipsilateral CST projections become maladaptive when they become abnormally dense and strong. We next discuss how animal studies support a developmental “competition rule” whereby more active/used connections are more competitive and overtake less active/used connections. Based on this rule, after unilateral injury the damaged CST is less able to compete for spinal synaptic connections than the uninjured CST. This can lead to a progressive loss of the injured hemisphere’s contralateral projection and a reactive gain of the undamaged hemisphere’s ipsilateral CST. Knowledge of the pathophysiology of the developing CST after injury informs interventional strategies. In an animal model of hemiplegic CP, promoting injured system activity or decreasing the uninjured system’s activity immediately after the period of a developmental injury both increase the synaptic competitiveness of the damaged system, contributing to significant CST repair and motor recovery. However, delayed intervention, despite significant CST repair, fails to restore skilled movements, stressing the need to consider repair strategies for other neural systems, including the rubrospinal and spinal interneuronal systems. Our interventional approaches harness neural activity-dependent processes and are highly effective in restoring function. These approaches are minimally invasive and are poised for translation to the human.